Preparation method and application of solid-liquid composite sulfide solid electrolyte

CN122968415APending Publication Date: 2026-10-23CHONGQING SAICIYAN LITHIUM NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611110579.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0005]为了解决上述接触不良、容易产生团聚和发生副反应等问题,本发明通过将氟化高浓度电解液稀释到完全非极性溶剂中,通过混合到对应粒度的硫化物固态电解质微纳米颗粒上实现分散均匀,再通过烘干得到表面附着氟化高浓度电解液的硫化物固态电解质的固液复合型硫化物固态电解质

Benefits of technology

本发明制备硫化物固态电解质表面附着一层氟化高浓度电极液层,可有效地降低固/固界面的接触,从而降低阻抗并提升离子电导率。而硫化物固态电解质的最大的问题在于其-2价的S元素具有较高的还原性,容易与高氧化性的元素反应,而氟代烷烃仅有C-C键、C-F键和C-H键,大大降低了与硫化物固态电解质可能发生副反应,从而使用高浓度氟代烷烃的电解液包覆硫化物固态电解质表面的同时,也提升了本发明固液复合型硫化物固态电解质的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a preparation method and application of a solid-liquid composite sulfide solid electrolyte. In the application, a fluorinated high-concentration electrolyte is diluted into a completely non-polar solvent, is uniformly dispersed on sulfide solid electrolyte micro-nanoparticles of a corresponding particle size through mixing, and is dried to obtain a solid-liquid composite sulfide solid electrolyte with the fluorinated high-concentration electrolyte attached to the surface of the sulfide solid electrolyte. The method not only solves the problem of uniform mixing in the synthesis process, but also solves the problems of high synthesis risk or high solvent residue caused by a single solvent method. The method not only realizes the synthesis of a pure-phase sulfide solid electrolyte product, but also provides a mass-producible sulfide solid electrolyte synthesis process, and has high application value for the actual production of sulfide solid electrolytes in the future.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the technical field of batteries, specifically to the preparation method and application of solid-liquid composite sulfide solid electrolytes. Background Technology

[0002] With the increasing demand for high-safety batteries in new energy vehicles, portable electronic devices, and energy storage systems, traditional liquid lithium-ion batteries, due to the flammability and side reactions of organic electrolytes, are unable to meet the requirements of next-generation energy storage technologies. All-solid-state batteries, which use solid electrolytes instead of liquid electrolytes, can fundamentally eliminate the safety hazards inherent in liquid lithium-ion batteries.

[0003] Currently, solid electrolytes mainly include three categories: polymer solid electrolytes, oxide solid electrolytes, and sulfide solid electrolytes. Among them, polymer solid electrolytes have the advantage of flexibility. They can achieve good contact at the positive and negative electrode interfaces through high flexibility, thereby reducing impedance. However, the disadvantage of polymer solid electrolytes is their extremely low ionic conductivity, which is only 10 Ω·cm at room temperature. -4 Solid-state batteries, operating at speeds on the order of S / cm, require heating to achieve good rate performance. Oxide solid-state electrolytes (OSEs) offer high stability, but their rigidity hinders good contact with the positive and negative electrode interfaces, significantly impeding battery performance. Sulfide solid-state electrolytes, on the other hand, are considered the most promising technology for industrialization due to their advantages: excellent ionic conductivity, approaching that of liquid electrolytes; good interfacial wettability with electrode materials, facilitating lithium-ion transport; and excellent processing performance, allowing for reduced interfacial impedance through cold pressing.

[0004] All-solid-state batteries consist of a positive electrode, a sulfide solid electrolyte film, and a negative electrode. The positive electrode is composed of positive active material (80-90 wt%), binder (0.5-2 wt%), conductive agent (0.1-0.5 wt%), and sulfide solid electrolyte (10-15 wt%). The role of the sulfide solid electrolyte is to ensure the transport channel of lithium ions. Therefore, the interfacial contact between the positive and negative electrodes and the sulfide solid electrolyte is an important step to ensure that lithium ions can be smoothly transported from the positive electrode to the negative electrode. However, poor contact is a common problem in practical applications. A conventional method to improve interfacial contact is to micronize the sulfide solid electrolyte, grinding large sulfide solid electrolyte particles into micro-nano particles of hundreds of nanometers. This increases the specific surface area by reducing the particle size, thereby increasing the contact area with the positive and negative electrodes. However, this method has the following side effects: First, excessive micronization of the sulfide solid electrolyte increases the surface energy of the micronized particles, leading to easy agglomeration during slurry preparation. Second, micronized sulfide solid electrolyte particles cannot solve the side reaction problems between the positive and negative electrodes. Therefore, a new sulfide solid electrolyte is urgently needed that can solve the poor contact problem without causing agglomeration or side reactions. Summary of the Invention

[0005] To address the aforementioned issues of poor contact, easy aggregation, and side reactions, this invention employs a method that dilutes a high-concentration fluorinated electrolyte into a completely non-polar solvent, then mixes it onto micro / nano particles of a corresponding particle size of sulfide solid electrolyte to achieve uniform dispersion. Finally, drying yields a solid-liquid composite sulfide solid electrolyte with a surface coated with the high-concentration fluorinated electrolyte. This method solves both the problem of uniform mixing during synthesis and the issues of high synthesis risk or high solvent residue associated with single-solvent methods.

[0006] Specifically as follows: A method for preparing a solid-liquid composite sulfide solid electrolyte includes the following steps: (1) Preparation of coarse particles: Electrolyte raw materials are prepared according to the stoichiometric ratio in the structural chemical formula of sulfide solid electrolyte, and coarse particles are obtained after coarse grinding, sintering, refining and sieving. (2) Preparation of micro and nano particles: The coarse particles are added to the first solvent and ground to obtain micro and nano slurry, which is then filtered to obtain micron-sized solid particles and / or the micro and nano slurry is finely ground to obtain nano-sized solid particles; (3) Add fluorinated electrolyte to the micron-sized solid particles and / or the nano-sized solid particles, mix until homogeneous, dry and crush to obtain the solid-liquid composite sulfide solid electrolyte. The chemical formula of the sulfide solid electrolyte is Li.6-a PS 5-a X 1+a , where 0≤a≤1, and X is one or more of F, Cl, Br, and I.

[0007] In some embodiments, the solid electrolyte structure is Li6PS5Cl, Li 5.9 PS 4.9 Cl 1.1、 Li 5.8 PS 4.8 Cl 1.2、 Li 5.7 PS 4.7 Cl 1.3、 Li 5.6 PS 4.6 Cl 1.4、 Li 5.5 PS 4.5 Cl 1.5、 Li 5.4 PS 4.4 Cl 1.6、 Li 5.3 PS 4.3 Cl 1.7、 Li 5.2 PS 4.2 Cl 1.8、 Li 5.1 PS 4.1 Cl 1.9、 Li5S4Cl2; Li6PS5F, Li 5.9 PS 4.9 F 1.1、 Li 5.8 PS 4.8 F 1.2、 Li 5.7 PS 4.7 F 1.3、 Li 5.6 PS 4.6 F 1.4、 Li 5.5 PS 4.5 F 1.5、 Li 5.4 PS 4.4 F 1.6、 Li 5.3 PS 4.3 F 1.7、 Li 5.2 PS 4.2 F 1.8、 Li 5.1 PS 4.1 F 1.9、 Li5S4F2; Li6PS5Br, Li 5.9 PS4.9 Br 1.1、 Li 5.8 P.S. 4.8 Br 1.2、 Li 5.7 P.S. 4.7 Br 1.3、 Li 5.6 P.S. 4.6 Br 1.4、 Li 5.5 P.S. 4.5 Br 1.5、 Li 5.4 P.S. 4.4 Br 1.6、 Li 5.3 P.S. 4.3 Br 1.7、 Li 5.2 P.S. 4.2 Br 1.8、 Li 5.1 P.S. 4.1 Br 1.9、 Li5S4Br2; Li6PS5I、Li 5.9 P.S. 4.9 I 1.1、 Li 5.8 P.S. 4.8 I 1.2、 Li 5.7 P.S. 4.7 I 1.3、 Li 5.6 P.S. 4.6 I 1.4、 Li 5.5 P.S. 4.5 I 1.5、 Li 5.4 P.S. 4.4 I 1.6、 Li 5.3 P.S. 4.3 I 1.7、 Li 5.2 P.S. 4.2 I 1.8、 Li 5.1 P.S. 4.1 I 1.9、 Li5S4I2; Li6PS5Cl 0.5 Br 0.5、 Li 5.7 P.S. 4.7 Cl 0.7 Br 0.6、 Li 5.5 P.S. 4.5 Cl 0.8 Br 0.7、 Li5.2 PS 4.2 Cl 0.9 Br 0.9、 Li6PS5Cl 0.45 Br 0.45 I 0.1、 Li 5.5 PS 4.5 Cl 0.7 Br 0.7 I 0.1、 Li 5.2 PS 4.2 Cl 0.8 Br 0.8 I 0.2、 Li6PS5Cl 0.4 Br 0.4 I 0.2、 Li 5.7 PS 4.7 Cl 0.6 Br 0.6 I 0.1、 Li6PS5F 0.1 Cl 0.4 Br 0.4 I 0.1、 Li 5.7 PS 4.7 F 0.1 Cl 0.6 Br 0.5 I 0.1 Or Li 5.2 PS 4.2 F 0.1 Cl 0.8 Br 0.8 I 0.1 .

[0008] Furthermore, the electrolyte raw material includes one or more of Li2S, P2S5, LiCl, LiBr, LiF, or LiI.

[0009] Further, the coarse grinding in step (1) is selected from ball mill, sand mill, vibratory mill or stirred mill. Preferably, the coarse grinding includes a first grinding and a second grinding, wherein the rotation speed and time of the first grinding are both less than those of the second grinding, and the first grinding and the second grinding are the same or different.

[0010] Furthermore, the grinding is selected from ball milling, preferably, the ball milling speed is 200rpm-600rpm, and the time is 1h-10h. In some specific embodiments, both the first and second grinding are ball milling processes. The first ball milling is performed at a speed of 180 rpm for 1 hour, and the second ball milling is performed at a speed of 300 rpm for 9 hours.

[0011] Furthermore, the sintering process in step (1) includes placing the ground raw material in an alumina crucible, heating it to a set temperature in an inert gas atmosphere, holding it at that temperature, and then cooling it down.

[0012] Furthermore, the sintering temperature is set at 400-550℃, and the holding time is 5h-20h.

[0013] In some embodiments, the set temperature is selected from 400°C, 410°C, 420°C, 430°C, 440°C, 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, or 550°C.

[0014] In some embodiments, the heat preservation time is selected from 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h or 20h.

[0015] Furthermore, the inert gas includes one or more of nitrogen, helium, neon, argon, krypton, xenon, or radon.

[0016] The "refinement" mentioned in this invention refers to the process of reducing the size of the sample after the sintering process. The method is not limited; conventional grinding can be used, and the sample is finally sieved through a 30-micron sieve to obtain coarse particles.

[0017] Further, in step (2), the first solvent is selected from one or more of toluene, p-xylene, m-xylene, o-xylene, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, butyl valerate, pentyl valerate, isopentyl isovalerate, anisole, petroleum ether, tetrahydrofuran, diphenyl ether, n-hexane, or n-heptane.

[0018] Furthermore, the grinding or fine grinding mentioned in step (2) is selected from ball mill, sand mill, vibratory mill or stirring mill, and the methods are the same or different.

[0019] Furthermore, both the grinding and the fine grinding are selected from ball milling.

[0020] Furthermore, the zirconium oxide grinding beads used for the grinding process have a particle size of 3mm-5mm, and the zirconium oxide grinding beads used for the fine grinding process have a particle size of 0.5mm-1mm.

[0021] Furthermore, the fine grinding time is longer than the grinding time.

[0022] Furthermore, the grinding and fine grinding speeds are 80-120 rpm, the grinding time is 2-4 hours, and the fine grinding time is 4-10 hours.

[0023] Furthermore, the filtration described in step (2) is selected from centrifugation, vacuum filtration or pressure filtration.

[0024] Furthermore, the fluorinated electrolyte in step (3) contains a diluent.

[0025] Furthermore, the diluent is a completely nonpolar straight-chain alkane.

[0026] The "completely nonpolar straight-chain alkane" mentioned in this invention refers to the δp (polarity term) MPa in the Hansen solubility parameter (HSP). 0 · 5 and δh (hydrogen bond term) MPa 0 · 5 All are 0.

[0027] Furthermore, the completely nonpolar straight-chain alkane is selected from n-pentane, n-hexane, or n-heptane.

[0028] Furthermore, the fluorinated electrolyte in step (3) comprises a solvent and a solute, wherein the solvent is a fluoroalkane and the solute is selected from LiPF6, LiFSI or LiTFSI.

[0029] Furthermore, the fluoroalkane is a straight-chain end-group substituted alkane, and even further, the fluoroalkane is a monofluoro, difluoro, or trifluoro substituted alkane.

[0030] In some specific embodiments, the fluoroalkane is selected from difluoropropane, 1-fluorobutane, 1,4-difluorobutane, 1-fluoropentane, 1,5-difluoropentane, 1,3,5-trifluoropentane, 1-fluorohexane, 1,6-difluorohexane, 1,3,6-trifluorohexane, 1-fluoroheptane, 1,7-difluoroheptane, or 1,4,7-trifluoroheptane.

[0031] Furthermore, the lithium salt concentration in the fluorinated electrolyte is 1-2 mol / L.

[0032] Furthermore, the dilution ratio of the diluting solvent is 1:9 to 1:99.

[0033] Furthermore, the drying temperature is 80-120℃, and the drying time is 4h-40h.

[0034] On the other hand, the present invention discloses a battery comprising a positive electrode, a negative electrode, and a sulfide solid electrolyte, wherein the sulfide solid electrolyte is prepared by the method described above.

[0035] Beneficial effects: This invention prepares a sulfide solid electrolyte with a high-concentration fluorinated electrode liquid layer on its surface, which effectively reduces solid / solid interface contact, thereby reducing impedance and improving ionic conductivity. The biggest problem with sulfide solid electrolytes is that their -2 valence sulfur atom has high reducing power and readily reacts with highly oxidizing elements. Fluorinated alkanes, however, only have C-C, C-F, and CH bonds, greatly reducing the possibility of side reactions with the sulfide solid electrolyte. Therefore, using a high-concentration fluorinated alkanes electrolyte to coat the surface of the sulfide solid electrolyte also improves the stability of the solid-liquid composite sulfide solid electrolyte of this invention. Detailed implementation method: To make the technical problems, solutions, and advantages of this invention clearer, a detailed description will be provided below with reference to specific embodiments. These embodiments are merely examples and represent one solution of this invention; the scope of protection of this invention is not limited to the following embodiments. Rather, the purpose of providing these embodiments is to provide a more thorough and comprehensive understanding of the disclosure of this invention.

[0036] Unless otherwise specified, the experimental methods described in the following examples are conventional methods in the art using default parameters and steps; the experimental materials used are commercially available products unless otherwise specified. Where specific techniques or conditions are not specified in the examples, they should be performed according to the techniques or conditions described in the literature in the art, or according to the corresponding product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased through legitimate channels.

[0037] The preparation method of solid-liquid composite sulfide solid electrolyte includes the following steps: (1) Preparation of coarse particles: Electrolyte raw materials are prepared according to the stoichiometric ratio in the structural chemical formula of sulfide solid electrolyte, and coarse particles are obtained after coarse grinding, sintering, refining and sieving. (2) Preparation of micro / nanoparticles: The coarse particles are added to the first solvent and ground to obtain a micro / nanoparticle slurry, which is then filtered to obtain micron-sized solid particles and / or The micro-nano slurry was finely ground to obtain nanoparticle solids; (3) Add fluorinated electrolyte to the micron-sized solid particles and / or the nano-sized solid particles, mix until homogeneous, dry and crush to obtain the solid-liquid composite sulfide solid electrolyte. The sulfide solid electrolyte has a Li structure. 6-a PS 5-a X 1+a , where 0≤a≤1, and X is one or more of F, Cl, Br, and I.

[0038] The electrolyte raw material includes one or more of Li2S, P2S5, LiCl, LiBr, LiF, or LiI.

[0039] The coarse grinding in step (1) is selected from ball mill, sand mill, vibratory mill or stirring mill.

[0040] The sintering process in step (1) includes placing the ground raw material in an alumina crucible, heating it to a set temperature in an inert gas atmosphere, holding it at that temperature, and then cooling it down.

[0041] Furthermore, the inert gas includes one or more of nitrogen, helium, neon, argon, krypton, xenon, or radon.

[0042] In step (2), the first solvent is one or more of the following solvents: toluene, p-xylene, m-xylene, o-xylene, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, butyl valerate, pentyl valerate, isopentyl isovalerate, anisole, petroleum ether, tetrahydrofuran, diphenyl ether, n-hexane, n-heptane.

[0043] The grinding or fine grinding mentioned in step (2) is selected from ball mill, sand mill, vibratory mill or stirring mill, and the methods are the same or different.

[0044] Furthermore, both the grinding and the fine grinding are selected from ball milling.

[0045] Furthermore, the filtration described in step (2) is selected from centrifugation, vacuum filtration or pressure filtration.

[0046] Furthermore, the fluorinated electrolyte in step (3) contains a diluent.

[0047] Furthermore, the diluent is a completely nonpolar straight-chain alkane.

[0048] Furthermore, the completely nonpolar straight-chain alkane is selected from n-pentane, n-hexane, or n-heptane.

[0049] Furthermore, the fluorinated electrolyte in step (3) comprises a solvent and a solute, wherein the solvent is a fluoroalkane and the solute is selected from LiPF6, LiFSI or LiTFSI.

[0050] Furthermore, the fluoroalkane is a straight-chain end-group substituted alkane, and even further, the fluoroalkane is a monofluoro, difluoro, or trifluoro substituted alkane.

[0051] Example 1: Preparation of a solid-liquid composite sulfide solid electrolyte The preparation method is as follows: (1) Preparation of coarse particles: According to the structural chemical formula of the sulfide solid electrolyte (Li 6-a PS 5-a X1+a 30g of electrolyte raw material was prepared according to the stoichiometric ratio of (where 0≤a≤1, and X is one or more of F, Cl, Br, and I). The raw material and 5mm zirconia ball milling beads were placed in a 500mL zirconia ball mill jar and ball milled at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. The precursor powder was placed in an alumina crucible and heated to 400-550℃ under an argon atmosphere for 5-20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, the sample was collected and thoroughly ground in a glove box, and then sieved using a 30-micron sieve to obtain coarse particles.

[0052] (2) Preparation of micro and nano particles: 25g of coarse particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball milling jar, and 3-10 times the mass of the first solvent of the coarse particles were added. The mixture was ball milled at 80rpm-120rpm for 2h-4h. After separation of the ball and the material, a slurry of micro and nano particles was obtained. Half of the slurry was filtered to obtain a micron particle filter cake. The remaining slurry was put back into a 500mL zirconia ball milling jar, and 500g of 0.5mm-1.0mm zirconia balls were added. The mixture was ball milled at 80rpm-120rpm for 4h-10h. After separation of the ball and the material, a slurry of nano particles was obtained. After filtration, a filter cake of nano particles was obtained.

[0053] (3) Preparation and mixing of high-concentration fluorinated electrolyte: The solute of the fluorinated electrolyte is dissolved in 10 mL of fluorinated electrolyte solvent, with a concentration of 1 mol / L-2.5 mol / L, and diluted with 9-99 times the volume of diluent. Add 4-18 mL of the diluted high-concentration fluorinated electrolyte to the micron-particle filter cake and the nanoparticle filter cake, respectively, and grind the micron-particle filter cake and the nanoparticle filter cake into a uniform slurry state using an agate grinding mortar.

[0054] (4) Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven to dry at a temperature of 80-120℃ for 4-40 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0055] To illustrate the advantages of the solid-liquid composite sulfide solid electrolyte preparation of the present invention, this embodiment conducted 13 sets of experiments and 4 sets of control experiments to demonstrate the advantages of the present invention in preparing a sulfide solid electrolyte with a high concentration of fluorinated electrode liquid layer using straight-chain fluorinated alkanes.

[0056] Specifically, it includes the groups shown in Table 0.

[0057]

[0058] The specific preparation method is as follows: Experimental group 1 1. Preparation of coarse particles: Li₂S, P₂S₅, and LiCl were prepared in stoichiometric ratios of 30g each (Li₆PS₅Cl). The raw materials and 500g of 5mm zirconia grinding beads were placed in a 500mL zirconia ball mill jar and milled at 180rpm for 1 hour, followed by milling at 300rpm for 9 hours to obtain precursor powder. The precursor powder was placed in an alumina crucible and heated to 550℃ under an argon atmosphere for 12 hours. The heating rate was 3℃ / min, and the cooling rate was 1.5℃ / min. After sintering, the Li₆PS₅Cl sample was collected and thoroughly ground in a glove box. The sample was then sieved using a 30μm sieve to obtain 29.5g of coarse LPSC particles.

[0059] 2. Preparation of micro / nanoparticles: 25g of coarse LPSC particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of toluene and 5g of ethyl acetate were added, and the mixture was ball-milled at 120rpm for 2 hours. After separation of the ball and material, a slurry of micro / nanoparticles was obtained. Half of the slurry was filtered to obtain a micron-sized filter cake. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 1.0mm zirconia balls were added. The mixture was ball-milled at 120rpm for 8 hours. After separation of the ball and material, a slurry of nanoparticles was obtained. After filtration, a filter cake of nanoparticles was obtained.

[0060] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of difluoropropane to a concentration of 2 mol / L, and then diluted with 100 mL of n-pentane. 5 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate grinding mortar.

[0061] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 80°C for 36 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0062] Experimental group 2 1. Preparation of coarse particles: Take Li₂S, P₂S₅, and LiCl in the form of Li 5.7 PS 4.7 Cl 1.3 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 520℃ under an argon atmosphere, holding it at that temperature for 14 hours. The heating rate is 3℃ / min, and the cooling rate is 1.5℃ / min. After sintering, collect the Li. 5.7 PS 4.7 Cl1.3 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSC. 1.3 Coarse particles.

[0063] 2. Preparation of micro / nanoparticles: LPSC 1.3 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of p-xylene and 5g of butyl acetate were added. The mixture was ball-milled at 100rpm for 2 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.8mm zirconia balls were added. The mixture was ball-milled at 100rpm for 12 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0064] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1-fluorobutane to a concentration of 2 mol / L, and then diluted with 120 mL of n-pentane. 6 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0065] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 90°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0066] Experimental group 3 1. Preparation of coarse particles: Take Li₂S, P₂S₅, and LiCl in the form of Li 5.5 PS 4.5 Cl 1.5 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 480℃ under an argon atmosphere, holding it at that temperature for 16 hours. The heating rate is 3℃ / min, and the cooling rate is 1.5℃ / min. After sintering, collect the Li. 5.5 PS 4.5 Cl 1.5 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.4 g of LPSC. 1.5 Coarse particles.

[0067] 2. Preparation of micro / nanoparticles: LPSC 1.525g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of m-xylene and 5g of butyl acetate were added. The mixture was ball-milled at 100rpm for 2 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.8mm zirconia balls were added. The mixture was ball-milled at 100rpm for 12 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0068] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiPF6 was dissolved in 10 mL of 1,4-difluorobutane to a concentration of 1 mol / L, and then diluted with 120 mL of n-hexane. 6 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0069] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 90°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0070] Experimental group 4 1. Preparation of coarse particles: Take Li₂S, P₂S₅, and LiCl in the form of Li 5.2 PS 4.2 Cl 1.8 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 460℃ under an argon atmosphere for 16 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect the Li. 5.2 PS 4.2 Cl 1.8 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.7 g of LPSC. 1.8 Coarse particles.

[0071] 2. Preparation of micro / nanoparticles: LPSC 1.825g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of o-xylene and 5g of butyl butyrate were added. The mixture was ball-milled at 80rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 80rpm for 20 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0072] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiTFSI was dissolved in 10 mL of 1-fluoropentane to a concentration of 1.5 mol / L, and then diluted with 500 mL of n-hexane. 15 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0073] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 100℃ for 40 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0074] Experimental group 5 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, and LiBr in the form of Li₆PS₅Cl 0.5 Br 0.5 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 530℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li6PS5Cl. 0.5 Br 0.5 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.7 g of LPSC. 0.5 B 0.5 Coarse particles.

[0075] 2. Preparation of micro / nanoparticles: LPSC 0.5 B 0.525g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of anisole and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 80rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 10 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0076] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,5-difluoropentane to a concentration of 2 mol / L, and then diluted with 990 mL of n-heptane. 18 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0077] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 110℃ for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0078] Experimental group 6 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, and LiBr in the form of Li 5.7 PS 4.7 Cl 0.7 Br 0.6 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat to 500℃ under an argon atmosphere, holding for 24 hours at a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.7 PS 4.7 Cl 0.7 Br 0.6 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.7 g of LPSC. 0.7 B 0.6 Coarse particles.

[0079] 2. Preparation of micro / nanoparticles: LPSC 0.7 B 0.625g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar, along with 100g of petroleum ether and 5g of amyl valerate. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.6mm zirconia balls were added. The mixture was ball-milled at 110rpm for 10 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0080] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiTFSI was dissolved in 10 mL of 1,3,5-trifluoropentane to a concentration of 1 mol / L, and then diluted with 90 mL of n-hexane. 5 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0081] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 110℃ for 20 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0082] Experimental group 7 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, and LiBr in the form of Li 5.2 PS 4.2 Cl 0.9 Br 0.9 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 460℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect the Li. 5.2 PS 4.2 Cl 0.9 Br 0.9 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSC. 0.9 B 0.9 Coarse particles.

[0083] 2. Preparation of micro / nanoparticles: LPSC 0.9 B 0.925g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of tetrahydrofuran and 5g of butyl valerate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a micron-particle filter cake. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.6mm zirconia balls were added. The mixture was ball-milled at 110rpm for 12 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a nano-particle filter cake was obtained.

[0084] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiTFSI was dissolved in 10 mL of 1-fluorohexane to a concentration of 1.5 mol / L, and then diluted with 90 mL of n-hexane. 4 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0085] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120℃ for 20 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0086] Experimental group 8 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, and LiI in the form of chemical formula Li₆PS₅Cl 0.4 Br 0.4 I 0.2 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 500℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li6PS5Cl. 0.4 Br 0.4 I 0.2 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSCl. 0.4 Br 0.4 I 0.2 Coarse particles.

[0087] 2. Preparation of micro / nanoparticles: LPSCl 0.4 Br 0.4 I 0.225g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of diphenyl ether and 5g of isoamyl isovalerate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and the material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.6mm zirconia balls were added. The mixture was ball-milled at 100rpm for 12 hours. After separation of the ball and the material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0088] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,6-difluorohexane to a concentration of 2 mol / L, and then diluted with 90 mL of n-hexane. 7 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0089] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry at 110℃ for 25 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0090] Experimental group 9 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, and LiI in the form of chemical formula Li 5.7 PS 4.7 Cl 0.6 Br 0.6 I 0.1 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 480℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.7 PS 4.7 Cl 0.6 Br 0.6 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSCl. 0.6 Br 0.6 I 0. 1. Coarse particles.

[0091] 2. Preparation of micro / nanoparticles: LPSCl 0.6 Br 0.6 I 0.1. 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of n-hexane and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0092] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,6-difluorohexane to a concentration of 2 mol / L, and then diluted with 90 mL of n-hexane. 8 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0093] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 110℃ for 28 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0094] Experimental group 10 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, and LiI in the form of chemical formula Li 5.2 PS 4.2 Cl 0.8 Br 0.8 I 0.2 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 450℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.2 PS 4.2 Cl 0.8 Br 0.8 I 0.2 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSCl. 0.8 Br 0.8 I 0.2 Coarse particles.

[0095] 2. Preparation of micro / nanoparticles: LPSCl 0.8 Br 0.8 I 0.225g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of n-heptane and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0096] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,3,6-trifluorohexane to a concentration of 2 mol / L, and then diluted with 90 mL of n-hexane. 6 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0097] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0098] Experimental group 11 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, LiI, and LiF in the form of chemical formula Li₆PS₅F. 0.1 Cl 0.4 Br 0.4 I 0.1 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 510℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li6PS5F. 0.1 Cl 0.4 Br 0.4 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSF. 0.1 Cl 0.4 Br 0.4 I 0.1 Coarse particles.

[0099] 2. Preparation of micro / nanoparticles: LPSF 0.1 Cl 0.4 Br 0.4 I 0.125g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of p-xylene and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0100] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1-fluoroheptane to a concentration of 2.5 mol / L, and then diluted with 90 mL of n-heptane. 5 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0101] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0102] Experimental group 12 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, LiI, and LiF in the form of Li 5.7 PS 4.7 F 0.1 Cl 0.6 Br 0.5 I 0.1 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 510℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.7 PS 4.7 F 0.1 Cl 0.6 Br 0.5 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.5 g of LPSF. 0.1 Cl 0.6 Br 0.5 I 0.1 Coarse particles.

[0103] 2. Preparation of micro / nanoparticles: LPSF 0.1 Cl0.6 Br 0.5 I 0.1 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of m-xylene and 5g of butyl butyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a micro / nano particle slurry was obtained. Half of the slurry was filtered to obtain a micron-sized filter cake. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a nanoparticle slurry was obtained. After filtration, a nanoparticle filter cake was obtained.

[0104] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,7-difluoroheptane to a concentration of 2 mol / L, and then diluted with 90 mL of n-heptane. 3 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0105] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0106] Experimental group 13 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, LiI, and LiF in the form of Li 5.2 PS 4.2 F 0.1 Cl 0.8 Br 0.8 I 0.1 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 510℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.2 PS 4.2 F 0.1 Cl 0.8 Br 0.8 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.5 g of LPSF. 0.1 Cl 0.8 Br 0.8 I 0.1 Coarse particles.

[0107] 2. Preparation of micro / nanoparticles: LPSF 0.1 Cl 0.8 Br 0.8 I 0.1 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of anisole and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0108] 3. Preparation and mixing of high-concentration fluorinated electrolyte: LiFSI was dissolved in 10 mL of 1,4,7-trifluoroheptane to a concentration of 2 mol / L, and then diluted with 90 mL of n-heptane. 8 mL of the diluted high-concentration fluorinated electrolyte was added to both the micron-particle and nanoparticle filter cakes, and the micron-particle and nanoparticle filter cakes were ground into a homogeneous slurry using an agate mortar.

[0109] 4. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0110] Control group 1 1. Preparation of coarse particles: Li₂S, P₂S₅, and LiCl were prepared in stoichiometric ratios of 30g each (Li₆PS₅Cl). The raw materials and 500g of 5mm zirconia grinding beads were placed in a 500mL zirconia ball mill jar and milled at 180rpm for 1 hour, followed by milling at 300rpm for 9 hours to obtain precursor powder. The precursor powder was placed in an alumina crucible and heated to 550℃ under an argon atmosphere for 12 hours. The heating rate was 3℃ / min, and the cooling rate was 1.5℃ / min. After sintering, the Li₆PS₅Cl sample was collected and thoroughly ground in a glove box. The sample was then sieved using a 30μm sieve to obtain 29.5g of coarse LPSC particles.

[0111] 2. Preparation of micro / nanoparticles: 25g of coarse LPSC particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of toluene and 5g of ethyl acetate were added, and the mixture was ball-milled at 120rpm for 2 hours. After separation of the ball and material, a slurry of micro / nanoparticles was obtained. Half of the slurry was filtered to obtain a micron-sized filter cake. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 1.0mm zirconia balls were added. The mixture was ball-milled at 120rpm for 8 hours. After separation of the ball and material, a slurry of nanoparticles was obtained. After filtration, a filter cake of nanoparticles was obtained.

[0112] 3. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 80°C for 36 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0113] Control group 2 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, and LiBr in the form of Li₆PS₅Cl 0.5 Br 0.5 Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 530℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li6PS5Cl. 0.5 Br 0.5 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.7 g of LPSC. 0.5 B 0.5 Coarse particles.

[0114] 2. Preparation of micro / nanoparticles: LPSC 0.5 B 0.5 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of anisole and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 80rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 10 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0115] 3. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 110℃ for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0116] Control group 3 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, and LiI in the form of chemical formula Li 5.7 PS 4.7 Cl 0.6 Br 0.6 I 0.1Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 480℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.7 PS 4.7 Cl 0.6 Br 0.6 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.6 g of LPSCl. 0.6 Br 0.6 I 0.1 Coarse particles.

[0117] 2. Preparation of micro / nanoparticles: LPSCl 0.6 Br 0.6 I 0.1 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of n-hexane and 5g of isobutyl isobutyrate were added, and the mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0118] 3. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 110℃ for 28 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0119] Control group 4 This embodiment provides a method for preparing a sulfide solid electrolyte, comprising the following steps: 1. Preparation of coarse particles: Take Li₂S, P₂S₅, LiCl, LiBr, LiI, and LiF in the form of Li 5.2 PS 4.2 F 0.1 Cl 0.8 Br 0.8 I 0.1Take 30g of the corresponding stoichiometric ratio, place the raw material and 500g of 5mm zirconia grinding beads into a 500mL zirconia ball mill jar, and ball mill at 180rpm for 1 hour, then at 300rpm for 9 hours to obtain precursor powder. Place the precursor powder in an alumina crucible and heat it to 510℃ under an argon atmosphere for 20 hours, with a heating rate of 3℃ / min and a cooling rate of 1.5℃ / min. After sintering, collect Li. 5.2 PS 4.2 F 0.1 Cl 0.8 Br 0.8 I 0.1 The sample was thoroughly ground in a glove box and sieved using a 30-micron sieve to obtain 29.5 g of LPSF. 0.1 Cl 0.8 Br 0.8 I 0.1 Coarse particles.

[0120] 2. Preparation of micro / nanoparticles: LPSF 0.1 Cl 0.8 Br 0.8 I 0.1 25g of coarse zirconia particles and 500g of 5mm zirconia balls were placed in a 500mL zirconia ball mill jar. 100g of anisole and 5g of isobutyl isobutyrate were added. The mixture was ball-milled at 120rpm for 4 hours. After separation of the ball and material, a slurry of micro- and nano-particles was obtained. Half of the slurry was filtered to obtain a filter cake of micron-sized particles. The remaining slurry was returned to the 500mL zirconia ball mill jar, and another 500g of 0.5mm zirconia balls were added. The mixture was ball-milled at 120rpm for 14 hours. After separation of the ball and material, a slurry of nano-particles was obtained. After filtration, a filter cake of nano-particles was obtained.

[0121] 3. Drying: Place the micron-sized particle slurry and the nano-sized particle slurry in a vacuum oven and dry them at 120°C for 30 hours. After drying, simply crush them to obtain micron-sized particles and nano-sized particles.

[0122] Example 2 Performance testing of sulfide solid electrolyte (1) Ionic conductivity test: 0.2g of solid electrolyte powder was poured into a 10mm diameter sleeve and compressed into a tablet using a tablet press at a pressure of 300MPa for 1 minute. The thickness L of the solid electrolyte disc was measured using a micrometer. A piece of carbon-coated copper foil (carbon end facing the solid electrolyte) was placed at each end of the solid electrolyte disc as blocking electrodes. The disc was then placed in a conductivity testing kit, pressurized to 300MPa, and connected to an electrochemical workstation for EIS testing. The intersection point of the EIS curve with the Y-axis was taken as the impedance Ω. The impedance was calculated using the formula: σ = L / (Ω*S), where S = π*R. 2Since R = 5 mm, then S = 0.785 cm. 2 The calculation should have yielded the (ionic + electronic) conductivity, but because the electronic conductivity is 6 orders of magnitude lower than the ionic conductivity, the resulting value is directly equivalent to the ionic conductivity.

[0123] The parameters for the EIS test of ionic conductivity are as follows: a DC voltage of 50 mV is applied, and the test is performed using the AC impedance method in the frequency range of 1 MHz to 1 Hz. The results are shown in Table 1. It can be seen from the table that the solid-liquid composite sulfide solid electrolytes prepared by experimental groups 1-13 in Example 1 have higher ionic conductivity than the single sulfide solid electrolytes prepared by control groups 1-4 under the same composition and particle size. This indicates that attaching a layer of high-concentration fluorinated electrode liquid to the surface of the sulfide solid electrolyte can effectively reduce the contact at the solid / solid interface, thereby reducing impedance and improving ionic conductivity.

[0124] (2) Particle size distribution of dry particle size analysis Take a sample of about 0.2g and place it on the dry particle size analyzer feeder. The feed is fed by shaking and grinding with metal balls to prevent the sulfide solid electrolyte powder from agglomerating before testing. The sulfide solid electrolyte powder is fed into the Omec dry particle size analyzer by purging with 0.6MPa high-pressure nitrogen gas and the results are obtained. The results are shown in Table 1.

[0125] Table 1. Particle size distribution and conductivity test results of sulfide solid electrolytes

[0126] Example 3: Application of sulfide solid electrolytes To gain a clearer understanding of solid-liquid composite sulfide solid electrolytes, the following mold battery experiments were conducted: Step 1: Take 100 mg of the sulfide solid electrolyte of the example or comparative example micron particles and cold press it into a sheet at 400 MPa in an alumina mold with a diameter of 10 mm. Step 2: Grind and mix 80% by mass of the NCM811 positive electrode and 20% by mass of the nanoparticles from the same embodiment or comparative example in Step 1. Take 21 mg of this mixture and spread it evenly on one side of the cold-pressed sheet from Step 1. Compact it using a press at 300 MPa. Grind and mix 60% by mass of the graphite negative electrode and 40% by mass of the nanoparticles from the same embodiment or comparative example in Step 1. Take 17 mg of this mixture and spread it evenly on the other side of the cold-pressed sheet from Step 1. Compact it using a press at 400 MPa. Connect the above mold battery to the Newwell battery testing system. The test parameters are as follows: charge / discharge range of 4.3V to 2.8V, charge / discharge rate of 0.1C for the first 3 cycles, and charge / discharge rate of 0.3C for the next 100 cycles. Table 2 Battery charge and discharge experiments

[0127] As can be seen from the table, the solid-liquid composite sulfide solid electrolyte prepared by the embodiments of the present invention effectively reduces the interfacial impedance during the charging and discharging process of the mold battery. In addition to improving the charge and discharge capacity and coulombic efficiency of the first cycle, the liquid electrolyte layer on the surface of the sulfide solid electrolyte will form a more stable interface layer with the positive and negative electrodes, thereby improving the discharge capacity retention rate over long cycles.

[0128] Although preferred embodiments have been described in this application, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of this application.

[0129] Obviously, those skilled in the art can make various modifications and variations to this application without departing from the spirit and scope of this application. Therefore, if such modifications and variations fall within the scope of the claims of this application and their equivalents, this application also intends to include such modifications and variations.

Claims

1. A method for preparing a solid-liquid composite sulfide solid electrolyte, characterized in that, Includes the following steps: (1) Preparation of coarse particles: Electrolyte raw materials are prepared according to the stoichiometric ratio in the structural chemical formula of sulfide solid electrolyte, and coarse particles are obtained after coarse grinding, sintering, refining and sieving. (2) Preparation of micro / nanoparticles: The coarse particles are added to the first solvent and ground to obtain a micro / nanoparticle slurry, which is then filtered to obtain micron-sized solid particles and / or The micro-nano slurry was finely ground to obtain nanoparticle solids; (3) Add fluorinated electrolyte to the micron-sized solid particles and / or the nano-sized solid particles, mix until homogeneous, dry and crush to obtain the solid-liquid composite sulfide solid electrolyte. The chemical formula of the sulfide solid electrolyte is Li. 6-a PS 5-a X 1+a , where 0≤a≤1, and X is one or more of F, Cl, Br, and I.

2. The preparation method according to claim 1, characterized in that, The electrolyte raw material includes one or more of Li2S, P2S5, LiCl, LiBr, LiF, or LiI.

3. The preparation method according to claim 1 or 2, characterized in that, In step (2), the first solvent is selected from one or more of toluene, p-xylene, m-xylene, o-xylene, ethyl acetate, butyl acetate, butyl butyrate, isobutyl isobutyrate, butyl valerate, pentyl valerate, isopentyl isovalerate, anisole, petroleum ether, tetrahydrofuran, diphenyl ether, n-hexane, or n-heptane.

4. The preparation method according to claim 1 or 2, characterized in that, The grinding or fine grinding in step (2) is selected from ball milling, sand milling, vibratory milling or stirring milling, and the methods are the same or different; preferably, the grinding and fine grinding are selected from ball milling; more preferably, the particle size of the zirconia ball milling beads used in the grinding is 3mm-5mm, and the particle size of the zirconia ball milling beads used in the fine grinding is 0.5mm-1mm.

5. The preparation method according to claim 1, characterized in that, The fluorinated electrolyte in step (3) contains a diluent; preferably, the diluent is a completely nonpolar straight-chain alkane; more preferably, the completely nonpolar straight-chain alkane is selected from n-pentane, n-hexane or n-heptane.

6. The preparation method according to claim 1 or 5, characterized in that, The fluorinated electrolyte in step (3) contains a solvent and a solute. The solvent is a fluoroalkane, and the solute is selected from LiPF6, LiFSI or LiTFSI.

7. The preparation method according to claim 6, characterized in that, The fluoroalkane is a straight-chain terminal substituted alkane; preferably, the fluoroalkane is monofluoro, difluoro, or trifluoro substituted; more preferably, the fluoroalkane is selected from difluoropropane, 1-fluorobutane, 1,4-difluorobutane, 1-fluoropentane, 1,5-difluoropentane, 1,3,5-trifluoropentane, 1-fluorohexane, 1,6-difluorohexane, 1,3,6-trifluorohexane, 1-fluoroheptane, 1,7-difluoroheptane, or 1,4,7-trifluoroheptane.

8. The preparation method according to claim 6 or 7, characterized in that, The lithium salt concentration in the fluorinated electrolyte is 1-2.5 mol / L.

9. The preparation method according to claim 5, characterized in that, The dilution ratio of the diluent solvent is 1:9 to 1:

99.

10. A battery comprising a positive electrode, a negative electrode, and a sulfide solid electrolyte, wherein the sulfide solid electrolyte is prepared by the method according to any one of claims 1-9.